Atypical presentations of histoplasmosis: hemolytic anemia. Case report and literature review - María Eugenia Landaeta; Sofía Mata-Essayag; Maria Teresa Colella; Vanessa Pineda; Joaquin Inaty (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2016)
Histoplasmosis is a granulomatous disease, produced by Histoplasma capsulatum. This fungus causes a wide range of clinical manifestations; the most common is the pulmonary form. In some cases, atypical presentations are described. Case report: a 70 year old male patient, from Barinas, Venezuela, who worked in a chicken farm, with diagnosis of histoplasmosis and hemolytic anemia is described. The patient improved with antifungal treatment. Conclusions: in Venezuela, an endemic area for this mycosis, clinicians must have a high suspicion index for this disease, taking into account risk factors, such as age and epidemiology. To our knowledge, this is the third case report in the literature.